Estimating the shape of economic crises under heterogeneity - Jonas Dovern; Nils Jannsen (Kiel Institute for the World Economy (IfW), 2009)
During the ongoing financial crisis the analysis of similar historical crises has gained more and more attention among economic researchers and forecasters. Existing studies, however, do not tackle the immense heterogeneity that is present in cross-country samples in a formal and consistent way. In this paper, we propose a standardization approach to estimate the typical impact of economic crises. We show that our approach leads to estimates that are much less dependent on the sample used to estimate the typical shape and, hence, should give more reliable information about the typical macroeconomic impact of economic crises.
Keywords: E17; E32; E44; E66; 330; Economic Crisis; Financial Crisis; Banking Crisis; Economic History; United States; Wirtschaftskrise; Finanzmarktkrise; Bankenkrise; Makroökonomischer Einfluss; Wirtschaftsgeschichte; Statistisches Auswahlverfahren; Welt; USA